Emerging investigator series: air conditioning filters as a sampler for semi-volatile organic compounds in indoor and near-building air - Jílková, Simona Rozárka; Melymuk, Lisa; Klánová, Jana (Environmental science. Processes & impacts, 2020)
Organic compounds like flame retardants (FRs), polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs) and polycyclic aromatic hydrocarbons (PAHs) are consistently found in both indoor and outdoor environments. There are many possible matrices for measurement of these compounds (e.g. indoor dust, air - passive and active air samples), but all methods have limitations, like the heterogeneous distribution of indoor dust, or noisy active air samplers. We used filters from building-wide heating, ventilation and air conditioning (HVAC) units to evaluate levels of PAHs, PCBs, OCPs and NFRs in indoor and outdoor environments, and to evaluate whether this method is feasible for screening semivolatile organic compounds (SVOCs) in indoor and near-building outdoor environments. Detectable levels of FRs, PCBs, OCPs and PAHs were found, demonstrating that HVAC filters do collect SVOCs, with generally higher levels of PAHs in the incoming air filters and higher levels of PCBs, OCPs and FRs in the outgoing air filters. Levels of FRs, PCBs and OCPs in outgoing air were comparable to those measured using conventional active air sampling in the same building. The advantages of using HVAC filters are (1) integrated and homogeneous samples, as the whole building is sampled over typically a long timescale (months), and (2) samples are easy and cheap to collect and do not require prior deployment of samplers. The key disadvantage is that HVAC filters are not designed for analytical chemistry and thus the filter materials can have variable or unknown gas sorption and particle capture, and can have strong matrix effects during analysis.
Keywords: klimatizace; polychlorované bifenyly; Air Pollution, Indoor; Flame Retardants; znečištění vzduchu ve vnitřním prostředí; vzduchové filtry; těkavé organické sloučeniny; Air Conditioning; látky znečišťující vzduch; Air Filters; Air Pollutants; Polychlorinated Biphenyls; polycyklické aromatické uhlovodíky; Volatile Organic Compounds; retardanty hoření; Polycyclic Aromatic Hydrocarbons; Environmental Monitoring; monitorování životního prostředí